Structure and excellent visible light catalysis of Prussian blue analogues BiFe(CN)6·4H2O. Issue 2 (3rd January 2018) - Gao, Qilong; Chen, Jun; Li, Qiang; Zhang, Ji; Zhai, Zhao; Zhang, Shantao; Yu, Ranbo; Xing, Xianran
Abstract : BiFe(CN)6 ·4H2 O, which exhibited a layered structure of FeC6 and BiN6 coordination polyhedra, was synthesised and exhibited excellent visible light catalytic activity. Abstract : Photo-Fenton catalysis with high-efficiency is required for the resolution of environmental pollution. Here, the Prussian blue analogue BiFe(CN)6 ·4H2 O with a narrow bandgap (1.63 eV) shows excellent visible light catalysis to decompose organic dyes and tetracycline. The microrod and nanoplate morphologies were successfully synthesized by simple precipitation with different additives. The nanoplates of BiFe(CN)6 ·4H2 O show excellent phono-Fenton catalytic activity meaning that RhB can be decomposed within 6 min in the presence of H2 O2 . BiFe(CN)6 ·4H2 O exhibits a layered structure, which consists of FeC6 and BiN6 coordination polyhedra. The zero field cooling indicated that BiFe(CN)6 ·4H2 O has an antiferromagnetic order at low temperatures. Furthermore, the stability of the BiFe(CN)6 ·4H2 O catalyst is very good, which has been investigated by various characterizations. The mechanism of the excellent catalysis is related to the crucial role of H2 O2, which inhibits the recombination of the electron–hole pair and drives the photo-Fenton reaction. Therefore, to treat the wastewater by photo-Fenton catalysis, the present component of BiFe(CN)6 ·4H2 O is a promising catalyst candidate.